1999
DOI: 10.1055/s-1999-2538
|View full text |Cite
|
Sign up to set email alerts
|

New Methods of Preparing Cyclopentenone Ketals: The Photosolvolysis of 3-Alkoxypyridinium Tetrafluoroborates

Abstract: A new base catalysed method of ketal formation is reported, such that substituted cyclopentenone ketals are prepared from 3-alkoxypyridinium tetrafluoroborate salts.The photochemical properties of aromatic compounds are a source of amazement to many organic chemists. In particular the metaphotocyclo addition 1 has often been described as the reaction that leads to the greatest increase in molecular complexity. This light induced reaction between an aromatic ring and an olefin was concurrently discovered in 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Other interesting observations have come from investigations reported by Penkett and Simpson in 1999. 33,34 As shown in Scheme 18, these workers observed that irradiation of alcoholic solutions of 1,6-dialkyl-3alkoxypyridinium tetrafluoroborates 59 containing NaOH leads to modestly to highly efficient (41-92%) production of the bicyclic ketals 61. Several features of these processes give additional insight into mechanistic and synthetic issues.…”
Section: Recent Studies Exploring the Scope And Generality Of Pyridin...mentioning
confidence: 99%
“…Other interesting observations have come from investigations reported by Penkett and Simpson in 1999. 33,34 As shown in Scheme 18, these workers observed that irradiation of alcoholic solutions of 1,6-dialkyl-3alkoxypyridinium tetrafluoroborates 59 containing NaOH leads to modestly to highly efficient (41-92%) production of the bicyclic ketals 61. Several features of these processes give additional insight into mechanistic and synthetic issues.…”
Section: Recent Studies Exploring the Scope And Generality Of Pyridin...mentioning
confidence: 99%
“…In addition, these workers showed that the products of these reactions undergo stereocontrolled, acid-promoted ring opening with a variety of nucleophiles (H 2 O, CH 3 OH, HOAc, HSAc). Since that time, a number of informative studies of these processes have been described. Also, unique applications of the bicyclic-aziridine ring forming and opening sequence to the synthesis of aminocyclitols, polyhydroxylated indolizidines, and amino-aldopentoses 15 have been reported.…”
mentioning
confidence: 99%